Pengaruh Transformasi Digital terhadap Kualitas Hasil Audit dengan Kompetensi Auditor sebagai Variabel Moderasi pada KAP Yogyakarta - Rafidah Rahadatul Aisy; Dewi Saptantinah Puji Astuti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Digital transformation brings significant changes in data processing, including the audit process carried out by auditors in producing quality audit reports. This study shows that auditors are required to be able to adapt to these changes, both in terms of skills and knowledge, in order to implement digital-based audit data processing programs. The data used this study were obtained through the distribution of questionnaires to Public Accounting Firms (KAP) in Yogyakarta. The research method applied was quantitative. The population of this study consisted of all auditore in 17 KAPs in Yogyakarta listed in the IAPI Directory in 2025, and the sample used was 67 respondents. The results indicate that digital transformation has a significant positive effect on audit quality, while auditor competence does not moderate the effect of digital transformation on audit quality.